Estimating the Elasticity of Intertemporal Substitution When Instruments Are Weak - Yogo, Motohiro (The Review of Economics and Statistics, 2004)
In the instrumental variables (IV) regression model, weak instruments can lead to bias in estimators and size distortion in hypothesis tests. This paper examines how weak instruments affect the identification of the elasticity of intertemporal substitution (EIS) through the linearized Euler equation. Conventional IV methods result in an empirical puzzle that the EIS is significantly less than 1 but its reciprocal is not different from 1. This paper shows that weak instruments can explain the puzzle and reports valid confidence intervals for the EIS using pivotal statistics. The EIS is less than 1 and not significantly different from 0 for eleven developed countries.